Risk of Cardiovascular Diseases Associated with PCOS in India: A Review - Kaur, Amandeep; Kumar, Ranjeet; Kumar, Hardik; Garg, Sonakshi; Vijukumar, Abhishek; Kumar, Dharmendra (Current Cardiology Reviews, 2025)
In the modern world, Polycystic Ovary Syndrome (PCOS) is thought to be the most prevalent endocrine condition affecting women. Compared to their normal counterparts, PCOS patients have higher rates of morbidity and death because they are more susceptible to these anomalies from an early age. Cardiovascular disease (CVD) and PCOS are prevalent in women. PCOS often results from a combination of hereditary and environmental causes. Insulin resistance (IR) is considered the primary cause of several metabolic risk factors, such as Type 2 Diabetes Mellitus (T2DM), Metabolic Syndrome (MetS), dyslipidemia, obesity, and hypertension (HTN). Additionally, patients with PCOS may also have elevated levels of non-traditional factors, including C-reactive protein (CRP), carotid intima-media thickness (IMT), coronary artery calcification (CAC), as well as endothelial dysfunction, which raises the likelihood of complications from CVD. This review utilizes statistics and data mostly sourced from research in India, offering insight into the nation's distinct PCOS prevalence and related cardiovascular risks. To lessen the impact of PCOS in the modern world, prompt identification and effective management of these warning signs with food, lifestyle changes, and/or medication are crucial. The research that examined the potential impact of PCOS on the most prevalent CVD-hypertension, insulin resistance, obesity, malignancy, diabetes mellitus, and dyslipidemia-is reviewed in this study. Measuring subclinical atherosclerosis, such as coronary artery calcium or carotid plaque, might help inform shared decision-making over the start of statin therapy when CVD risk is unknown.
Keywords: diabetes mellitus